Evaluation of post-thaw quality of brown-swiss and holstein bull semen diluted with different extenders - Serpil Sariozkan; Purhan Barbaros Tuncer; Mustafa Numan Bucak; Serhat Buyukleblebici; Huseyin Kinet; Ali Bilgen (Eurasian Journal of Veterinary Sciences)
Aim: To evaluate post-thaw guality of Brown-Swiss and Holstein bull semen diluted with different extenders. Materials and Methods: Ejaculates obtained from Holstein (n=36) and Brown-Swiss (n=36) bulls were divided into three aliquots and diluted with Tris-based, Optidyl® and Bioxcell® extenders, respectively. Thereafter they were frozen and thawed following a standard protocol. The effectiveness of freezing extenders was assessed according to postthaw sperm motility, acrosomal and total abnormalities and plasma membrane integrity. Results: With respect to Holstein bull semen, the highest percentages of sperm subjective (p<0.01), CASA progressive (p<0.001), and CASA motility (p<0.001) were found in semen diluted with Optidyl®. Optidyl® extender also provided best protection in terms of acrosome and plasma membrane integrity compared to other extenders (p<0.001). For motility motion including VAP, VSL and LIN values, the highest values were obtained from Optidyl and Tris (p<0.05). With respect to, the lowest percentages of post-thaw subjective (p<0.01), CASA motility (p<0.001) and membrane integrity (p<0.001) were obtained in the semen samples diluted with Bioxcell®. The percentage of progressive motility was found to be higher in Optidyl® than Bioxcell® (p<0.01). The highest percentages of acrosomal and total abnormalities were found in semen diluted with Bioxcell and Tris extenders. The highest ALH value was obtained from Optidyl® extender compared to the other groups (p<0.05). Conclusion: Optidyl® extender may be preferred rather than Bioxcell® or Tris + egg yolk extenders for freezing the Holstein and Brown-Swiss bull semen.